Mid-term outcome following revision surgery of clavicular non- and malunion using anatomic locking compression plate and iliac crest bone graft - Beirer, Marc (BMC Musculoskelet Disord, 2017)
BACKGROUND: Treatment of clavicular non- and malunion is still challenging. Current surgical procedures often result in frustrating functional outcome along with high-grade subjective impairment and increased rates of revision surgery. However, the combination of biological augmentation with vital bone graft and a biomechanically sufficient fixation system seems to be a promising concept of treatment. METHODS: In this retrospective study, 14 patients with a mean age of 44 years (26–67 years) suffering from non-union (n = 11) and/or malunion (n = 3) of the clavicle were enrolled. All patients were surgically treated using an anatomical precontoured locking compression plate (LCP) and autologous iliac crest bone graft. Functional outcome was assessed using the age- and sex-specific relative Constant Score. RESULTS: Mean follow-up was 27 months (range 12–44 months). The relative Constant Score significantly improved from preoperative 61 ± 8 (43–72) to 82 ± 10 (65–100) points at the final follow-up examination (p < 0.05). All patients showed bony union radiographically. One patient presented with a re-fracture of the clavicle nearly 3 years after revision surgery and 5 weeks after implant removal. Secondary fractures at the donor site of the anterior superior iliac spine were recorded in two patients. CONCLUSIONS: Iliac crest bone graft and anatomic locking plate fixation allow for a safe and adequate stabilization and radiographical bony union in non- and malunions of the clavicle with a high degree of patient satisfaction. However, secondary fractures of the anterior superior iliac spine constitute relevant complications and the time of hardware removal should be considered carefully.